Differential contextual factors of comorbid conduct and depressive disorders in Spanish children. - Ezpeleta L; Granero R; Doménech JM (European Child & Adolescent Psychiatry, 2005)
OBJECTIVE: The aim of this study was to clarify the validity of the mixed conduct/depressive disorder in young people to justify its place in ICD-10 by examining a wide range of risk factors, school performance and other contextual variables. METHOD: Data on risk factors and other school and family variables were compared between 66 referred children with depressive disorders without conduct disorder, 135 with conduct or oppositional defiant disorder without depressive disorders, and 90 with both. Data were obtained through structured diagnostic interviews with parents and children and questionnaires. RESULTS: Marked differences emerged between depressive and comorbid groups in rearing style, school and friends. Comorbid conduct-depression and pure conduct disorders share similar contextual factors; the differences are larger in school, where the pure conduct group has more difficulties. CONCLUSIONS: Based on contextual factors, pure depression is different from conduct-depressive disorder, but pure conduct disorder is similar to the comorbid condition. The results have implications for nosology and treatment of these disorders.